LIVING HADIS: KESEIMBANGAN NAFKAH LAHIR DAN BATIN DALAM MEMPERTAHANKAN HUBUNGAN SUAMI ISTRI DI KELURAHAN PECALUKAN, KECAMATAN PERIGEN, KABUPATEN PASURUAN - Qorrie Cornea Sunarto; Durrotun; Nasrulloh (al-Afkar, Journal For Islamic Studies, 2022)
Relationships in husband and wife relationships are needed to create a family that is sakinah, mawaddah, warohmah so that it is very necessary for husbands and wives to become husbands and wives who are obedient to religion and follow all the prescribed commands and prohibitions by Allah SWT. One form of effort to maintain a good relationship between husband and wife is the fulfillment of their rights and obligations as husband and wife, especially in matters of fulfilling clothing, food, shelter by husbands and wives who must always obey and fulfillment of sexual rights by husbands and wives. This study aims to determine the balance of physical and mental livelihoods of husband and wife to maintain the integrity of the household in Pecalukan Village, Prigen District, Pasuruan Regency. The research method in this paper uses empirical research which uses the method of analysis using the study of living hadith and a sociological approach. From this description, the results show that the relationship between husband and wife will be better when the balance between physical and mental living is fulfilled.